Meta-analysis of Big Five personality traits in autism spectrum disorder. (April 2019) - Lodi-Smith, Jennifer; Rodgers, Jonathan D; Cunningham, Sara A; Lopata, Christopher; Thomeer, Marcus L
The present meta-analysis synthesizes the emerging literature on the relationship of Big Five personality traits to autism spectrum disorder. Studies were included if they (1) either (a) measured autism spectrum disorder characteristics using a metric that yielded a single score quantification of the magnitude of autism spectrum disorder characteristics and/or (b) studied individuals with an autism spectrum disorder diagnosis compared to individuals without an autism spectrum disorder diagnosis and (2) measured Big Five traits in the same sample or samples. Fourteen reviewed studies include both correlational analyses and group comparisons. Eighteen effect sizes per Big Five trait were used to calculate two overall effect sizes per trait. Meta-analytic effects were calculated using random effects models. Twelve effects (per trait) from nine studies reporting correlations yielded a negative association between each Big Five personality trait and autism spectrum disorder characteristics (Fisher's z ranged from –.21 (conscientiousness) to –.50 (extraversion)). Six group contrasts (per trait) from six studies comparing individuals diagnosed with autism spectrum disorder to neurotypical individuals were also substantial (Hedges' g ranged from –.88 (conscientiousness) to −1.42 (extraversion)). The potential impact of personality on important life outcomes and new directions for future research on personality in autism spectrum disorder are discussed in light of results.